The consequences of modernity - Giddens, Anthony (Stanford Stanford University Press, 1990)
In this major theoretical statement, the author offers a new and provocative interpretation of institutional transformations associated with modernity. What is modernity? The author suggests, "As a first approximation, let us simply say the following: 'modernity' refers to modes of social life or organization which emerged in Europe from about the seventeenth century onwards and which subsequently became more or less worldwide in their influence."
Based on the Raymond Fred West memorial lectures which the author delivered at Stanford University in April 1988.
Keywords: Social structure